Analysis of Indonesia's Foreign Policy during President Jokowi - Muhammad Budiana (Institute of Computer Science (IOCS), 2022)
The foundational tenets of a nation's foreign policy could have their origins in the nation's history, ideology, or even the national constitution. However, the manner in which it is put into effect is heavily impacted by particular political objectives, leadership, and dynamics both domestically and internationally. In this paper, an attempt is made to investigate Indonesia's foreign policy during the administration of President Joko Widodo, also known by his nickname Jokowi. In this investigation, a qualitative strategy is combined with a descriptive research approach. The findings of the study indicate that economic diplomacy was the primary emphasis of Indonesia's foreign policy under the administration of President Joko Widodo, with the ultimate goal of establishing Indonesia as a leading economic power on the global stage in the not too distant future. In addition, President Joko Widodo's foreign policy, as stated in his Nawacita program, wants to make Indonesia a World Maritime Axis, which, if successfully realized, will have a significant impact on the progress of the country. If successfully realized, this goal will have a significant impact on the progress of the country.